Erratum: An Exploration of Food Insecurity, Poverty, Livelihood and Local Food Potentials in Kulon Progo Regency, Indonesia - Widiyanto, Dodi (Universitas Muhammadiyah Surakarta, 2018)
This erratum aims to revise a mistake from the previous article (Widiyanto, 2018). The mistake is mainly about the presentation of a table for the Appendix 3, i.e. Local Food Production Potential. There was a mistake for the Ngestiharjo village Local Food Production Potential figure, particularly for the tuber/uwi (column 8th). The correct value for this is provided here.